2008
DOI: 10.1111/j.1553-2712.2008.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparity in Analgesic Treatment of Emergency Department Patients with Acute Abdominal Pain

Abstract: Objectives: Oligoanalgesia for acute abdominal pain historically has been attributed to the provider's fear of masking serious underlying pathology. The authors assessed whether a gender disparity exists in the administration of analgesia for acute abdominal pain.Methods: This was a prospective cohort study of consecutive nonpregnant adults with acute nontraumatic abdominal pain of less than 72 hours' duration who presented to an urban emergency department (ED) from April 5, 2004, to January 4, 2005. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
159
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(181 citation statements)
references
References 35 publications
13
159
4
5
Order By: Relevance
“…[1][2][3] Optimal pain management is lacking in most EDs, as many patients do not receive analgesia [3][4][5][6][7][8][9][10][11][12] and time to analgesic administration is often too long. 3,[5][6][7][8][10][11][12][13][14][15][16][17][18][19] Most health care professionals underestimate pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Optimal pain management is lacking in most EDs, as many patients do not receive analgesia [3][4][5][6][7][8][9][10][11][12] and time to analgesic administration is often too long. 3,[5][6][7][8][10][11][12][13][14][15][16][17][18][19] Most health care professionals underestimate pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In emergency department (ER) and primary care visits for pain, studies have demonstrated that African Americans and women are less likely to receive opioids for acute pain. 12,[15][16][17] These racial differences are thought to contribute to the disproportionate effect of the opioid epidemic on the white population. 18 The influence of the social determinants of health cannot be fully explored without addressing socioeconomic status (SES).…”
mentioning
confidence: 99%
“…Young age (,2 years) and female gender are also linked with ED oligoanalgesia, and therefore were adjusted for in our models. 13,14 Patients' pain and triage level at presentation are clinical factors that can influence diagnostic test ordering and administration of analgesics. 15,16 Pain was measured on a 10-point scale and grouped into 4 categories: none (0), mild (1-3), moderate (4-6), and severe (7)(8)(9)(10) 17 For our analyses, we collapsed triage level into 3 groups: immediate or emergent, urgent, and semiurgent or nonurgent.…”
Section: Covariatesmentioning
confidence: 99%